KONSEP DIRI DAN PERILAKU KOMUNIKASI WARIA DI PEKANBARU - Andi Meirizal; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Transvestites as a part of society deserve equal treatment as other people, on the one hand should be placed as social reality that can not be denied. On the other side, their existence for some people in Indonesia is still considered as behavior deviation and a marginalized community, and also underestimated. This research aims to determine the self concept and communication behavior of the transvestites in Pekanbaru City. How the self concept of transvestites is phisically, mentally, and socially in both positive and negative perceptions, and how to conduct interpersonal communication of the transvestites in verbal and non-verbal communication. This research used qualitative research methods with a presentation of descriptive analysis. Data collection techniques used were observation, interview, and documentation. In achieving the validity of the data in this study, researcher used participatory extension and triangulation. The subject was the transvestites in Pekanbaru City, and the object was self concept and communication behavior of the transvestites in communicate between each other in interaction of interpersonal communication. The result shows that perceptions of the transvestites’ self concept physically, mentally, and socially in positive and negative way in Pekanbaru City was based on some factors, such as family background, financials, environment, and their own experience. Researcher also found their interpersonal communication between each other in verbal and non-verbal were varies, and they used symbols to do their interraction.Key word: Transvestites, self concept, interpersonal communication